Peran Pertumbuhan Ekonomi, Produksi Padi, dan Bantuan Pangan dalam Menurunkan Prevalensi Ketidakcukupan Konsumsi Pangan di Indonesia - Retno Windarti Auwalina; Mohammad Wasil (Jurnal Ekonomika : INDEPENDEN, 2026)
This study aims to examine the effects of GRDP per capita, harvested rice area, and food social assistance on the prevalence of food consumption inadequacy across Indonesian provinces during the period 2018–2024. The study employs a quantitative approach using panel data regression analysis covering 38 provinces over seven years. The data are obtained from official institutions, including Statistics Indonesia and relevant government agencies. Data estimation is conducted using a Fixed Effect Model based on model specification tests. The results indicate that GRDP per capita, harvested rice area, and food social assistance jointly have a significant effect on food consumption inadequacy. Partially, GRDP per capita has a significant effect in reducing food consumption inadequacy, while harvested rice area shows a marginal effect and food social assistance does not have a significant impact. These findings suggest that regional economic improvement plays a more dominant role in addressing food consumption inadequacy, whereas agricultural performance and food social assistance programs require further strengthening to effectively support food security. Keywords: GRDP per capita; rice harvest area, food social assistance; food consumption inadequacy; panel data JEL : H53, Q12, Q18, R11